Protective Effect of Rosa roxburghii Compound Plant Beverage on Acute Alcohol-induced Liver Injury in Mice - Zhengfang QI; Donghai LI; Yichun SUN; Xiaosheng YANG; Juan YANG; Rongrong ZHANG; Yu WANG; Xiong PAN; Chaoju ZHANG; Lilang LI (Shipin gongye ke-ji)
To study the protective effect of Rosa roxburghii Tratt compound plant beverage (RTCPB) against the acute alcoholic liver injury in mice, alcoholic liver injury models were established with 53% alcohol in male ICR mice using oral gavage. The drug was administered continuously for 21 days, the liver index, the content of triglyceride (TG), the activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) contents were determined to evaluate the potential protective effect of RTCPB on acute alcohol-induced liver injury in mice. Meanwhile, the pathology analysis was performed on liver tissue to determine pathological changes. The results showed that the liver indices of mice in silymarin control and RTCPB groups were significantly decreased (P<0.05) compared with the model group. Moreover, the RTCPB group showed the largest decrease of 11.78%, and the levels of AST, ALT, and TG in RTCPB high-dose group were significantly reduced by 50.70%, 40.43%, and 24.64% in serum, respectively. The activities of CAT, SOD and the content of GSH-Px in liver tissues were significantly increased by 33.14%, 24.87%, 135.04%, and MDA content was significantly reduced by 29.90%. The liver pathological section indicated that the RTCPB groups could alleviate the liver injury, especially for high dose group of RTCPB. Therefore, RTCPB possessed the protective effects on alcohol-induced acute liver injury.